FAKTOR-FAKTOR YANG MEMPENGARUHI PELAJAR SMP MENGEMUDIKAN SEPEDA MOTOR TANPA MEMILIKI SURAT IZIN MENGEMUDI (SIM) STUDI SMP NEGERI 34 PEKANBARU - Anggilia Gustiana; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research is relied on phenomenon to the number of collision of traffic conducted by student of SMP riding motorbike without Driving Licence (SIM). This research to know factors of what causingstudent SMPN 34 Pekanbaru riding motorbike Driving Licence (SIM). Method used in this research is descriptive qualitative with research focus: describe of factors causingstudent SMPN 34 Pekanbaru riding motorbike to their school. Technic of data collecting used by observation, interview by key person informan and and also the archives documentation from SMPN 34 Pekanbaru.Based on result of research and solution to object research that is factors causingstudent SMP riding motorbike without Driving Licence (SIM) can conclusion of internal factor causing student of SMPN 34 Pekanbaru riding motorbike to school there are 1) divisible motivation for reason of student to cost effective transportation and give pecking order (high prestige) they broughtly is kendaraan to school. 2) studentdiscipline attitude at school which is generally have [done/conducted] discipline collision at school and also in elapsing to traffic rules. Eksternal factor of influencing student of SMPN 34 Pekanbaru riding motorbike to school there are 1) weakness social control from school, socialize and parent in observing student SMPN 34 Pekanbaru by giving good facility in the form of their motorbike place of park and also the penalization inexistence for student ride the motor. 2) there is nothing medium of adequate transportation and on schedule which can be used [by] all student to go to school.keywords: student of SMPN 34 Pekanbaru, internal factor and eksternal factor.